2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2016
DOI: 10.1109/icassp.2016.7472566
|View full text |Cite
|
Sign up to set email alerts
|

Reference-based compressed sensing: A sample complexity approach

Abstract: We address the problem of reference-based compressed sensing: reconstruct a sparse signal from few linear measurements using as prior information a reference signal, a signal similar to the signal we want to reconstruct. Access to reference signals arises in applications such as medical imaging, e.g., through prior images of the same patient, and compressive video, where previously reconstructed frames can be used as reference. Our goal is to use the reference signal to reduce the number of required measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The CS theory can be modified so as to leverage a signal correlated to the signal of interest, called side information (SI), which is assumed to be provided a priori at the decoder in order to aid reconstruction [15], [16], [22]- [26]. In particular, the decoder aims at recovering the signal x based on the measurements y, the measurement matrix A and a side information vector, say w, which is correlated with s. The problem of CS with side information can be expressed via the following 1 − 1 optimization problem [15], [16], [24]…”
Section: Introductionmentioning
confidence: 99%
“…The CS theory can be modified so as to leverage a signal correlated to the signal of interest, called side information (SI), which is assumed to be provided a priori at the decoder in order to aid reconstruction [15], [16], [22]- [26]. In particular, the decoder aims at recovering the signal x based on the measurements y, the measurement matrix A and a side information vector, say w, which is correlated with s. The problem of CS with side information can be expressed via the following 1 − 1 optimization problem [15], [16], [24]…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, we have extended their theoretical analysis to our setting. 50 In particular, we developed a bound on the number of measurements required for perfect reconstruction of x with high probability in the presence of a reference. We also show that adding weights highly improves the results in comparison to other nonweighted ℓ 1 -minimization based solutions.…”
Section: A Theoretical Justificationmentioning
confidence: 99%
“…Hence, the estimation error was recovered instead of the sparse signal. The problem of CS with prior information was studied in [15][16][17], where, through bounds and geometrical interpretations, it was shown that 1 -1 minimization improves the performance of CS if the SI is of good enough quality.…”
Section: Introductionmentioning
confidence: 99%